2020
DOI: 10.1175/jas-d-19-0185.1
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum

Abstract: This corrigendum improves upon the size-dependent representation of graupel and hail terminal velocities, kinetic energies, and mass fluxes that were reported in the Heymsfield et al. (2018) study. In particular, representation of these dependencies on diameter over the full range of particle sizes is improved upon by correcting minor errors and by developing representations that cover different size ranges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 6 publications
(5 reference statements)
3
15
1
Order By: Relevance
“…That is, C D decreases with increasing size and mass (see also Figure 7). Nevertheless, the curve of Heymsfield et al [27] is in good agreement with our data showing an average deviation of 10 % for the arbitrarily chosen q4 long hailstone. The curve for spherical hailstones given in Rasmussen and Heymsfield [28] results in the lowest values of Re, which is due to the use of a constant drag coefficient of 0.6.…”
Section: Reynolds Number-best Numbersupporting
confidence: 92%
See 3 more Smart Citations
“…That is, C D decreases with increasing size and mass (see also Figure 7). Nevertheless, the curve of Heymsfield et al [27] is in good agreement with our data showing an average deviation of 10 % for the arbitrarily chosen q4 long hailstone. The curve for spherical hailstones given in Rasmussen and Heymsfield [28] results in the lowest values of Re, which is due to the use of a constant drag coefficient of 0.6.…”
Section: Reynolds Number-best Numbersupporting
confidence: 92%
“…This is also supported by our results which show that the drag for spheres is constant until at least Re = 10 4.85 (see Figure 4). Conversely, the decreasing trend of C D with increasing Re of the Wang et al [12] data was also found for natural hailstones by Heymsfield et al [27] which is indicated by the gray dashed curve in Figure 7.…”
Section: Drag Coefficientssupporting
confidence: 72%
See 2 more Smart Citations
“…Hail with diameters between 1 and 1.9 cm may cause some damage to vineyards and orchards (Dessens et al ., 2007; Morel, 2014; Brown et al ., 2015; Rasuly et al ., 2015) while hail with diameters larger than 2 cm damage cars, roofs, and cause severe damage to plants and crops. The impact speed of 2 cm hail varies between 55 and 65 kmh −1 (Heymsfield et al ., 2020). The impact of hail larger than 3 cm is to damage buildings and cars (Rasuly et al ., 2015).…”
Section: Methodsmentioning
confidence: 99%